Preventive Diplomacy and Conflict Prevention: Obstacles and Opportunities - Steven A. Zyck; Robert Muggah (Stability : International Journal of Security and Development, 2012)
Preventive diplomacy, conflict prevention and other forms of preventive action intended to stop armed conflicts before they escalate to widespread violence are the subject of intense debate. And despite their elevation to a norm in the United Nations, where they have been debated in the General Assembly and addressed in prominent reports from the Secretary-General, preventive diplomacy and conflict prevention continue to face daunting obstacles. Drawing from recent high-level consultations on the topic, this piece considers some recurrent obstacles and emerging opportunities in relation to preventive action.